1993
DOI: 10.1038/eye.1993.143
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser photorefractive keratectomy for myopia: 12 month follow-up

Abstract: SUMMARYA prospective study of excimer laser photo refractive ker atectomy was performed with the aim of correcting a range of myopic errors between -1.00 and -10.00 dioptres . Corneal healing was monitored through the first post-operative year by serial assessments of refrac tion, contrast sensitivity, corneal haze, pachymetry and keratometry. Eighty-one patients were recruited for the study. At 12 months 81 % were within ± 1.00 dioptre of desired emmetropia and with unaided vision of 6/12.Contrast sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Over the past two years these findings have been confirmed by other centres using different laser systems (table I) 28 30 33 39 40 41 42 43 44 45. Most myopic people have less than −6.00 dioptres of myopia, and in these patients predictability and stability of refractive outcome are relatively good 24 25 26 27 28 30 33 39 40 41 42 43 44 45. In addition, while photorefractive keratectomy has side effects (box 1), few sight threatening complications have been encountered 23 34.…”
Section: Excimer Laser Photorefractive Keratectomysupporting
confidence: 65%
See 3 more Smart Citations
“…Over the past two years these findings have been confirmed by other centres using different laser systems (table I) 28 30 33 39 40 41 42 43 44 45. Most myopic people have less than −6.00 dioptres of myopia, and in these patients predictability and stability of refractive outcome are relatively good 24 25 26 27 28 30 33 39 40 41 42 43 44 45. In addition, while photorefractive keratectomy has side effects (box 1), few sight threatening complications have been encountered 23 34.…”
Section: Excimer Laser Photorefractive Keratectomysupporting
confidence: 65%
“…Gartry et al, however, reported considerable individual variation in response to this treatment because of differences in wound healing from patient to patient, and in particular they found that it was much more difficult to treat moderate to high myopia (greater than around −6.00 D) 24 25 26. Over the past two years these findings have been confirmed by other centres using different laser systems (table I) 28 30 33 39 40 41 42 43 44 45. Most myopic people have less than −6.00 dioptres of myopia, and in these patients predictability and stability of refractive outcome are relatively good 24 25 26 27 28 30 33 39 40 41 42 43 44 45.…”
Section: Excimer Laser Photorefractive Keratectomymentioning
confidence: 93%
See 2 more Smart Citations
“…[1][2][3][4] In this study, we found that a reduction in contrast sensitivity signifi cantly correlated with the surgically induced increases in ocular higher order wavefront aberrations. Because there was no case of moderate to severe corneal subepithelial haze in our patients, the current data indicate that increases in ocular higher order wavefront aberrations led to a decline of contrast sensitivity function after PRK.…”
Section: Discussionmentioning
confidence: 83%